The effect of debt securities issuance towards equity market behavior in Malaysia - Chin , Sze Kim; Nur Adiana Hiau Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2012)
The study investigates the impact of debt securities issuance on the equity market behavior of the issuers. Event study results reveal that overall debt securities issuers experience an increase in equity return and a decrease in systematic risk, while total risk remains unchanged. The further examination of the 100 debt securities issuing companies finds significant differences between hybrid and non-hybrid debt securities issues. Hybrid debt securities experience a significant increase in equity return, decline in systematic risk and increase in total risk. Non-hybrid debt securities issues, however, are found to have no impact on equity market behavior The findings of the study imply that the general decline in systematic risk for debt securities issuing companies could motivate the issuance of debt securities, particularly the hybrid type, and thus improve market liquidity. Further non-hybrid debt securities may not be the appropriate alternative for sending a market signal as no impact on market behavior is found following the issuance.